Assessing the Quality of Human Immunodeficiency Virus Care in Nursing Homes. Issue 6 (13th February 2020) - Olivieri‐Mui, Brianne; McGuire, Jean; Griffith, John; Cahill, Sean; Briesacher, Becky
Abstract : BACKGROUND: Quality of human immunodeficiency virus (HIV) care in nursing homes (NHs) has never been measured. DESIGN: A cross‐sectional study. SETTING: NHs. PARTICIPANTS: A total of 203 NHs and 1375 persons living with HIV. MEASUREMENTS: Medicare claims from 2011 to 2013 were linked to assessments of resident health, prescription dispensing data, and national reports of NH characteristics. Five nationally validated HIV care quality measures (prescription of antiretroviral therapy; CD4/viral load monitoring; frequency of medical visits; gaps in medical visits; and Pneumocystis pneumonia prophylaxis) were adapted and applied to NHs. Logistic regression predicted compliance by organizational factors. Random intercept logistic regression predicted if persons living with HIV received care by person and organizational factors. RESULTS: Compliance ranged from 43.3% (SD = 31.1%) for CD4/viral load monitoring to 92.4% (SD = 13.6%) for gaps in medical visits. More substantiated complaints against an NH decreased the likelihood of high compliance with CD4/viral load monitoring (odds ratio [OR] = 0.846; 95% confidence interval [CI] = 0.726‐0.986), while NH‐reported incidents increased the likelihood of high compliance with pneumocystis pneumonia prophylaxis (OR = 1.173; 95% CI = 1.044‐1.317). Differences between NHs explained 21.2% or less of variability in receipt of care. CONCLUSIONS: Since 2013, the population with HIV and NH HIV care quality has inevitably evolved; however, this study provides previously unknown baseline metrics on NH HIV care quality and highlights significant challenges when measuring HIV care in NHs. J Am Geriatr Soc 68:1226–1234, 2020.